The State Defense Form Through Cultural Education On Energy Saving - Khotimah, Khusnul (Jurnal Pertahanan dan Bela Negara, 2017)
Abstract â€“ A strong country is a nation that has a united citizen in defending, fighting and protecting the country from all kinds of threats that occur, both military and non-military through awareness of defending the state for the integrity of the territory of Republic of Indonesia (NKRI). The concept of defending the state can be realized through energy-efficient culture education for the sustainability of Indonesia’s energy in the future. This article is intended to apply energy efficient and rational culture through the application of basic energy-saving values which include: (1) development of green education curriculum through energy conservation materials (efficient, wise and energy savvy); (2) developing the concept of energy-saving lifestyle habits in two directions (learning from student to student so that active student participation) such as turning off energy source equipment (tap water, lamp, AC) when they are not used continuously with assistance from educator which will become a positive habit that is embedded from childhood to use energy efficiently and rationally. The energy-saving culture education is not only a normative appeal, but there must be clear regulation on energy saving through cooperation between Ministry of Research and Technology and Ministry of Energy and Mineral Resources and Ministry of Defense. Therefore, the development culture of energy application continuously can be created with commitment from all academic society of education state defenses. Keywords: defending the state, energy conservation, education